The effect of adding sweet bean (Foeniculum vulgare) and Roselle (Hibiscus sabdariffa) seed powder on the digestibility coefficient and some growth parameters in common carp Cyprinus carpio: ??????? ???????? (NTU Journal of Agriculture and Veterinary Science, 2024)
Seven experimental diets were designed to feed fish of the common carp species Cyprinus carpio L.This diet, known as the control T1,is additive-free. Three other diets were added to sweet bean seeds in three different amounts: 0.5, 1,1.5% for the diets T2,T3,T4, respectively. Throughout a 60-day experiment, the percentages of Gujarat seed powder used in the T5, T6,T7 diets were 0.5,1,1.5%, respectively.The maximum digestibility factor was achieved by treatmentT6 89.44%,while treatments T2 and T7 gave digestibility factors of (84.02% and 83.38%), respectively.In terms of thermal growth coefficient reaching 0.022%. Treatments T1and T7 followed, with 0.017,0.013 percent, respectively.The metabolic growth rate for treatment T5 was most significant at 9.1 gm/kg/day, with treatments T1,T7 coming in second and third, respectively, at 6.9 and 5.6 gm/kg/day. The study concludes that adding currants and sweet bean powder to fish meals enhances the nutritional content of the diets while.